Turkish macroeconomic cycles in the EU perspective: a convergence discussion - Öztok, Gamze (My University, 2005)
Bu tezde Türkiye'nin makroekonomik döngüleri ve AB sürecinde birlik ekonomilerine ne kadar yakınsadığı araştırılmaktadır. İlk bölümde konjonktürel dalgalanma teorileri incelenirken, ikinci bölümde oynaklık ve korelasyon testleri yapılmıştır. GSYİH, büyüme, sabit sermaye yatırımları ve cari denge araştırma yapılan ana makroekonomik büyüklüklerdir. Yapılan testler ve araştırma sonucunda, Türkiye'nin sözkonusu olan değişkenler gözönünde bulundurulduğunda AB ekonomilerinden farklı hareket ettiği ortaya çıkmıştır. Kısa dönemde AB ekonomilerine bir yakınsama olmayacağına dair bir sonuca varilmıştır. The thesis studies the macroeconomic cycles in Turkey deliberating the convergence subject in the context of EU. The question of the thesis is if the Turkish economy approaches to EU economies in the frame of growth, GDP, Investment and current account balance variables. The quantitative analysis of the paper includes volatility, correlation and cross correlation analysis. It has been found that growth, investment and current account balance are not strongly correlated with the union economies while the GDP is. On the volatility front economic aggregates of Turkey fluctuates less than the average of the selected country group. Finally it is concluded that Turkish economy is a bit far to represent the common fundamentals of bloc economies and approach to EU. In the thesis it is concluded that the GDP of Turkey does not significantly comoves with EU. The GDP cycles do not have much to say for EU cycles and vice versa. The current account balance and investment patterns are related to EU story. As the GDP increases the current account deficit increases with a financing strategy by the FDI in line with considering the EU story as an anchor.
Keywords: Ekonomi; Makro ekonomi; Makroekonomi